Safety Voting System Based on D-S Evidence Theory - Yue Xi; Feng Liu; Hongli Yuan; Dongbo Pan (Institute of Advanced Engineering and Science, 2013)
This thesis proposes a safety instrument system which is based on D-S evidence theory, including sensor, logic voting system and execution unit. While the logic voting system concludes the input circuit, processor, output circuit and the diagnosis module based on D-S evidence theory. According to the diagnosis module in multi-channel logic voting system and calculation based on D-S evidence theory, the interconnected feedback information can improve the reliability of the diagnosis. Therefore, the safety instrument system elaborated in this thesis can achieve system’s self-diagnosis function under the premise of using less hardware equipment and at the mean time acquiring advantages of low cost, reliability and high security. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3510